Trends of early-onset colorectal cancer biomarkers from 1985 to 2024 : a bibliometric analysis - Hamzah Haryo Prakoso; Andre Setiawan; Nur Rahadiani (Universa Medicina, 2026)
Early-onset colorectal cancer (EOCRC) is increasingly recognized as a global public health concern. Biomarker research in EOCRC has expanded across hereditary, molecular, epigenetic, liquid biopsy, microbiome, and multi-omics domains, but the overall research landscape remains fragmented. This study aimed to map global research trends and identify prominent and underdeveloped topics in EOCRC biomarker research. A bibliometric analysis was conducted using publications on EOCRC biomarkers retrieved on October 27, 2024. Eligible documents were limited to English-language articles, reviews, and conference proceedings, with a final publication stage and no restriction on publication year. After screening, 134 relevant documents published between 1985 and 2024 were included. Bibliometric indicators, including publication trends, leading contributors, influential publications, topic evolution, and keyword co-occurrence patterns, were analyzed using Biblioshiny (Bibliometrix R package v4.1.3) and VOS viewer (v1.6.18). Early-onset colorectal cancer  biomarker research showed steady growth, with an annual growth rate of 7.54% and a publication peak in 2023. The dataset included 134 documents from 92 sources and involved 1,121 authors, with international collaboration observed in 20.9% of publications. Earlier studies focused mainly on hereditary predisposition, Lynch syndrome, mismatch repair genes, and microsatellite instability. More recent research shifted toward molecular profiling, epigenetic alterations, liquid biopsy, gut microbiota, tumor microenvironment, and multi-omics approaches. Underdeveloped areas included diagnostic biomarker validation, screening implementation, gut microbiota, risk factors, and machine learning-based biomarker discovery. Overall, EOCRC biomarker research has evolved from a hereditary-centered focus toward a broader precision oncology framework, but further work is needed to strengthen validation, translational relevance, and clinical applicability across diverse populations.